Application Program Chair - Michael-Grigoriou, Despina (My University, 2026)
euroxr-association.org/conference2023/committees-chairs-2https://www.euroxr-association.org/conference2023/committees-chairs-2/prepare CFP, review papers, final decisions on acceptance